2015
DOI: 10.1177/0963662515602406
|View full text |Cite
|
Sign up to set email alerts
|

Citizen science on a smartphone: Participants’ motivations and learning

Abstract: Citizen science provides researchers means to gather or analyse large datasets. At the same time, citizen science projects offer an opportunity for non-scientists to be part of and learn from the scientific process. In the Dutch iSPEX project, a large number of citizens turned their smartphones into actual measurement devices to measure aerosols. This study examined participants' motivation and perceived learning impacts of this unique project. Most respondents joined iSPEX because they wanted to contribute to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
137
4
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(154 citation statements)
references
References 33 publications
10
137
4
3
Order By: Relevance
“…Many projects are explicitly designed to have citizen scientists experience the scientific processes; thus, Bonney et al [2009] concluded that most citizen-science projects are designed to help citizen scientists learn scientific knowledge to some degree. Consistent with these efforts, volunteers of citizen-science projects reported that they actually learned about science by participating in the projects [e.g., Brossard, Lewenstein and Bonney, 2005;Land-Zandstra et al, 2016a;Masters et al, 2016].…”
Section: Learning About Sciencementioning
confidence: 84%
See 2 more Smart Citations
“…Many projects are explicitly designed to have citizen scientists experience the scientific processes; thus, Bonney et al [2009] concluded that most citizen-science projects are designed to help citizen scientists learn scientific knowledge to some degree. Consistent with these efforts, volunteers of citizen-science projects reported that they actually learned about science by participating in the projects [e.g., Brossard, Lewenstein and Bonney, 2005;Land-Zandstra et al, 2016a;Masters et al, 2016].…”
Section: Learning About Sciencementioning
confidence: 84%
“…For example, citizen scientists in Zooniverse projects often classify scientific data. Recent surveys and interviews show that citizen science volunteers are motivated to participate in projects by the opportunity to contribute to science [e.g., Brossard, Lewenstein and Bonney, 2005;Land-Zandstra et al, 2016a;Land-Zandstra et al, 2016b;Reed et al, 2013]. The possibility to contribute to science has emerged as a major motivation in several studies.…”
Section: Contributing To Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…Cooperation requires a thorough understanding of their background, motivations and goals. Understanding why citizen scientists make the commitment they do, and ensuring responsiveness to their concerns and motivations, is necessary if we are to take their engagement seriously (Land-Zandstra et al 2016). This includes citizen scientists' views on data sharing, which are rarely studied empirically.…”
Section: The Aims Of This Studymentioning
confidence: 99%
“…More use of online surveys, see for example, [84,85], may help to better meet the needs of citizens in the future. For example, how can citizens be encouraged to map an area that has already been mapped in the last few years or be more actively engaged in change detection mapping?…”
mentioning
confidence: 99%